Factors influencing sustainable software practices and the moderating role of knowledge accessibility: Evidence from the Malaysian electronic industry - Giweze, Chukwuyem; Abdul Aziz, Nor Azah; Arshad, Yusri (SAGE Publications Ltd, 2024)
The current study investigates factors influencing sustainable software practices due to the growing concern for environmental desolation in software sustenance among software practitioners in the electronic industry. It validates the GREEN SOFT Reference Model in the Malaysian context by conducting a study in Selangor, Malaysia, using non-probability sampling techniques. The research involved 250 employees from various software departments. Partial least square via SmartPLS3.3 examined the constructs of governance, software strategy, knowledge accessibility, software practitioners, sustainable environmental practices and sustainable software practices. Empirical results show that the GREEN SOFT Reference Model positively and directly influenced software practices, including software strategy, software practitioners, sustainable environmental practices and knowledge accessibility. However, knowledge accessibility moderated the link between software strategy and sustainable software practices. The other factors did not indicate the moderating effect. The research shows that knowledge accessibility has the most substantial impact compared to the other factors. Therefore, the study suggests that practitioners should pursue sustainable software practices to enhance effectiveness in the workplace. The study presents the theoretical and practical implications for future consideration.